Survival investing : how to prosper amid thieving banks and corrupt governments - Talbott, John R., 1955- (Palgrave Macmillan, 2012)
"Most individuals and institutions hold the preponderance of their investments in common stocks, corporate bonds, mutual funds, index funds, muni bonds, money markets, bank CDs, and Treasury securities. But these conventional investments will not do well in a world dominated by corrupt, debt-laden governments and thieving bankers, brokers and middlemen. Finance guru John R. Talbott, prescient predictor of the financial crisis and the housing market crash, offers a new paradigm for the coming economic reality. He shows how the recent housing collapse and global economic crisis left governments of the world with enormous annual operating deficits at a time when the banking system continues to struggle with bad debts and requires additional government guarantees and bailouts. Add the fact that growth is constrained because the first wave of the baby boom is hitting 65 and consumers are still loaded with unsustainable levels of debt, and you have a recipe for an economic catastrophe. In this uncertain atmosphere, Talbott offers clear strategies on what you can do to protect your investments and your family. Among the global dynamics covered are: *the low-wage threat of China and India *the legitimacy of gold investing *the false security of diversification *the risks of sovereign debt. and why most economists are missing the boat"--